The percentage change and differences in sport: a practical easy tool to calculate - Merino-Munoz, P.; Perez-Contreras, J.; Aedo-Munoz, E. (Sport Performance & Science Reports, 2021)
Efforts to draw up adequate inferences in sports science have long been focused through two main approaches, on the one hand the Null Hypothesis Significance Tests and in the other hand Magnitude-Based Inferences (1), however, many coaches consider calculation methods and software`s used in this process, complex. This document is aimed at showing a practical and easy method for coaches to analyze this data.